Convergence across subnational regions of Bangladesh – what the night lights data say?. (2022) - Basher, Syed Abul; Behtarin, Jobaida; Rashid, Salim
Abstract: We examine economic convergence among subnational regions of Bangladesh over the period 1992–2013. Unavailability of the traditional gross domestic product (GDP) for subnational areas and building on findings of recent luminosity literature, we use night lights intensity as a proxy for local economic activity to test the convergence hypothesis. Our results show the existence of both absolute and conditional convergence in night lights intensity, but with a very long half-life of convergence. Moreover, the results also indicate sigma divergence. Together, these findings suggest that regional disparity is persistent and wide across Bangladesh's 544 upazilas (subdistricts). There is evidence that lagging upazilas are catching up with the better off ones, but many are also converging with their neighbors or peers (a phenomenon known as "club convergence"). Overall, consistent with the evidence from studies on regional inequality in Bangladesh, our results also indicate that there is an "east-west" divide in luminosity across the subnational units in Bangladesh.